Sharia Monetary Policy as an Instrument for Inflation Control and Exchange Rate Stability Based on Sharia Economic Law: Bank Indonesia's Role in the Islamic Financial System - Ahmad Rifai; Yadi Janwari; Sofian Al-Hakim (Lembaga Yasin AlSys, 2026)
Islamic monetary policy in Indonesia faces the challenge of demonstrating its effectiveness in controlling inflation and maintaining exchange rate stability amid the dominance of conventional monetary instruments within a dual financial system. This study aims to analyze the role of Islamic monetary policy as an instrument for inflation control and exchange rate stabilization from the perspective of Islamic economic law, with a particular focus on the role of Bank Indonesia in the Islamic financial system. Using a qualitative-descriptive approach, the research examines the framework of Islamic monetary policy, central bank operational instruments, and relevant macroeconomic data. The findings indicate that Islamic monetary instruments, such as Bank Indonesia Syariah Certificates (SBIS), sharia SBSN repos, and sharia monetary operations are effective in managing liquidity without relying on interest rate mechanisms. Absorbent instruments are shown to be more effective in suppressing inflation, while injective instruments support economic growth during periods of slowdown. In addition, Islamic monetary policy indirectly contributes to exchange rate stability by strengthening domestic liquidity conditions and reducing speculative activities. The study concludes that sharia monetary policy is not only aligned with the legal principles of Islamic economics but also possesses empirical relevance as a macroeconomic stabilization instrument. The implications highlight the need for institutional strengthening and further deepening of the Islamic financial market so that Islamic monetary policy can play a more optimal role in supporting equitable and sustainable national economic stability.